Herpes simplex virus Vmw65-octamer binding protein interaction: a paradigm for combinatorial control of transcription. - Goding, C; O'Hare, P (1989)
The transcriptional status of a given viral or cellular gene is determined both by the availability of functional transcription factors and by the combination and spatial arrangement of the cis-acting elements to which they bind. While differential gene expression can be achieved to some extent by the interaction of different factors with different genes it is clear that in some cases the same factor is required for the regulation of genes that are not coordinately expressed. How a transcription factor achieves selective function in the absence of selective binding is a question that remains largely unanswered. The recent advances in understanding how both protein-protein and protein-DNA interactions are required to mediate the induction of herpes simplex virus immediate early (HSV IE) gene expression have highlighted a novel mechanism for combinatorial control of transcription which has significant implications for the differential control of cellular gene expression.